Quality of life in an Italian cohort of people living with HIV in the era of combined antiretroviral therapy (Evidence from I.A.N.U.A. study-investigation on antiretroviral therapy). Issue 11 (2nd November 2017) - Venturini, A.; Cenderello, G.; Di Biagio, A.; Giannini, B.; Ameri, M.; Giacomini, M.; Montefiori, M.; Setti, M.; Mazzarello, G.; Merlano, C.; Orcamo, P.; Viscoli, C.; et al.
ABSTRACT: The aims of this study were to assess the Health Related Quality of Life (HRQoL) of People Living with HIV/AIDS (PLWHA) who attend outpatient services in Genoa, Italy, and to evaluate the relationship between HRQoL and clinical factors, primarily: CD4+ cell count, viral load and HIV-Hepatitis C Virus (HCV) coinfection. A cross-sectional study was performed involving a sample of 943 consecutive patients. Firstly the EuroQol-Five Dimensions-Three Level (EQ-5D-3L) self-reported questionnaire was used to evaluate HRQoL, while socio-demographic information was collected using a separate self-administered questionnaire. Descriptive statistical analysis was then used to show the socio-demographic and clinical characteristics of the sample. Having characterized the sample, Pearson's correlation technique was used to assess the relationship between HRQoL and socio-demographic and clinical characteristics. Finally, multivariable linear regression was used to determine factors associated with HRQOL. The median EQ-Visual analogue scale (EQ-VAS) score was 75.4 (SD 18.4). We found statistically significant associations between the EQ-VAS score and age, coinfection with HCV+, education, other drugs taken over cART, hospitalization due to HIV and a CD4+ cell count <200 mm 3 compared with CD4+ cell count >500 mm 3 . Factors independently associated with lower HRQoL were: older age, coinfection with HCV+, other drugs used in addition to cART, hospitalization due to HIV and CD4+ cell count <200 mm 3 compared with CD4+ cell count >500 mm 3 .